Análise do polimorfismo dos genes TP53 E CYP1A1m1 em biópsia de endométrio de pacientes com endometriose - Silva, Ana Manoela Maria da (2012)
Endometriosis is a benign gynecological disease estrogen dependent that affects women at reproductive age. It is characterized by the presence of endometrial tissue outside the uterine cavity designated as ectopic endometrium, involving chronic inflammation in the pelvic cavity. The four stages of endometriosis are classified as: minimal (stage I), mild (stage II), moderate (stage III) or severe (stage IV). Symptomatology of endometriosis may vary and includes chronic pelvic pain and infertility. The etiology of endometriosis is uncertain and many studies are focusing on the associations between endometriosis and polymorphic mutations of several genes, such as CYP1A1m1 and TP53 genes. The aim of the present study was to evaluate the possible correlation between endometriosis and polymorphisms of CYP1A1m1 and TP53 genes. The study group consisted of 21 women diagnosed with endometriosis which endometrial biopsies were collected as samples. The control group included samples of peripheral blood of 42 women without symptoms related to the disease. Genotypes were determined by PCR and RFLP (Restriction Fragment Length Polymorphism) assays. The frequency of homozygote wild genotype w1/w1 in patients diagnosed with endometriosis (n=21) was 57% and 43% for w1/m1+m1/m1 genotypes. In the control group the frequencies were 86% for w1/w1 genotype and 14% for w1/m1+m1/m1 genotype. Fisher s test demonstrated that the association between the disease and the m1 mutant allele was statistically significant (p=0,01). The result is consistent with other studies reporting that the presence of genotype w1/w1 decreases the incidence of the disease. As for the TP53 polymorphism in the endometriosis group, the frequency of genotype Arg/Arg was 38%, 52% for Arg/Pro and 10% for Pro/Pro genotypes. In the control group the frequencies observed were 57% for the Arg/Arg; 43% for Arg/Pro and 0% for Pro/Pro. The x² test showed no significant difference in the result (p=0,07). Genotype variation among the samples of peripheral blood and endometrial biopsy on the TP53 gene was evaluated. The difference was not statistically significant (p=0,50). The m1 mutant allele of the gene CYP1A1m1 is a possible candidate molecular marker for endometriosis, regardless severity.